Strength enhancement of an aluminum alloy through high pressure torsion - Okeke, Uchechi; Yilmazer, Hakan; Sato, Shigeo; Boehlert, Carl J. (ELSEVIER SCIENCE SA, 2019)
High-pressure torsion (HPT) was used to investigate the potential of grain refinement and strengthening achievable for aluminum alloy 2139-T8. Discs of 20 mm diameter and approximately 0.9 mm thickness were HPT processed at room temperature under an applied pressure of 5 GPa after 1, 2, 4 and 8 revolutions. Microstructural characterization of the HPT-processed discs showed the formation of a sub-micron grain structure after one revolution. The HPT processing led to an exceptional increase of the hardness and tensile strength after only one revolution as well as a relatively homogenous microstructure containing refined grains. Some grain growth occurred with increasing number of revolutions. X-ray diffraction line profile analysis suggested dislocation arrangements consistent with the microstructural evolution and strengthening behavior. Overall, this study confirmed that there is a potential for using HPT for manufacturing Al 2139 with enhanced hardness and tensile strength.
Keywords: High-pressure torsion; Severe plastic deformation; Ultrafine-grained; MICROSTRUCTURAL EVOLUTION; MECHANICAL-PROPERTIES; THERMAL-STABILITY; GRAIN-REFINEMENT; AL-MG; DEFORMATION-BEHAVIOR; CONTRAST FACTORS; TITANIUM-ALLOY; PURE ALUMINUM; DISLOCATION; Science & Technology - Other Topics; Materials Science; Metallurgy & Metallurgical Engineering